TO INCREASE THE ROLE PLAY THE PARTICIPATION OF STUDENTS LEARNING MANAGEMENT MIDWIFERY IN POLTEKKES SURAKARTA - Firly Ratnawati; Kuswati .; Gita Kostania (STIKES DUTAGAMA KLATEN, 2014)
Background: Participation could encourage students to develop a thought for students learning to achieve the objective, it is necessary for the purpose of learning methods are increasing partisispasi with role play. Purpose: According to the draft of the problems that exist in these studies the objectives to be achieved are to see an increase in student participation in the management of midwifery rmenggunakan method with role play. Method: This is a research studies the class consists of two cycles to the plan, as follows execution observation, and the reflections. Result: There is an increase in student participation as evidenced by an increase in the percentage of each indicator includes student attendance for the planning of cycle I to cycle II was increased 25 %, to the presence of implementation and discussion has increased 10 %, the process of implementing role-play for the actual problem, a problem related to the student, problem solving is problematic, and there has been a problem since the first cycle reaches 100 %, the preparation of the script of the first cycle there is an increase of 25 % kesiklus II, there is an increase in infrastructure 50 %, the suitability of the cast from the first cycle kesiklus II increased 50 %, the effectiveness of the behavior of the cycle I kesiklus II increased by 25 %, increased appreciation of 35 %, corresponding dialogue plays increased 30 %, from the first cycle to the second cycle of conformity has reached 100 %. The next result is motivated student to student attention from the first cycle to the second cycle has increased 25 %, the student who recorded an increase of 20%, a student who believes an increase of 20%, students 10 % daydreaming first cycle and two cycles no student is daydreaming, students who busy themselves for the first cycle and second cycle 15 % no students busy themselves, and students were present at the time the process is no sleepy learners and annoy your friends. Conclution : Role play method can increase student participation in the learning process obstetric management is evidenced by the increase in the percentage of each indicator includes student attendance, process execution role play and student motivation.